2014
DOI: 10.1111/jphp.12158
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of drugs in mutant Nagase analbuminemic rats and responses to select diuretics

Abstract: Objectives To report (1) the pharmacokinetics of drugs that are mainly metabolized via hepatic cytochrome P450s (CYPs) or mainly excreted via the urine and bile, (2) the mechanism for the urinary excretion of drugs (such as glomerular filtration or renal active secretion or re-absorption), and (3) the diuretic effect of some loop diuretics in mutant Nagase analbuminaemic rats (NARs), an animal model for human familial analbuminaemia based on the pharmacokinetics of drugs reported in the literatures. Key findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Some of the above findings were also made in Nagase analbuminemic rats (Lee et al, 2013). Nagase analbuminemic rats are natural mutant Sprague-Dawley rats, which do not express Alb due to a single splice variant in the albumin gene.…”
Section: Albumin-deficient Animal Modelsmentioning
confidence: 61%
See 1 more Smart Citation
“…Some of the above findings were also made in Nagase analbuminemic rats (Lee et al, 2013). Nagase analbuminemic rats are natural mutant Sprague-Dawley rats, which do not express Alb due to a single splice variant in the albumin gene.…”
Section: Albumin-deficient Animal Modelsmentioning
confidence: 61%
“…In contrast to the above-mentioned mouse models, Nagase rats have been used to study the pharmacokinetics of drugs normally bound to Alb and other plasma proteins. For example, Lee et al (2013) report that a large number of drugs (e.g., furosemide, azosemide, bumetanide, torasemide, omeprazole, gliclazide, and warfarin) are weakly bound to plasma proteins in Nagase rats, and that their total body clearance are increased by 170% to more than 1,000%. Toyama et al (2014) found that intravenous administration of sunitinib also had increased systemic clearance in analbuminemic rats.…”
Section: Albumin-deficient Animal Modelsmentioning
confidence: 99%